Unveiling MHC-DAB Polymorphism Within the Western Balkan Salmonid Hotspot: Preliminary Outcomes from Native Trouts of Ohrid Lake and the Drin-Skadar Drainage (Albania) - Lorenzo Talarico; Arnold Rakaj; Lorenzo Tancioni (Biology)
Due to their involvement in pathogen-mediated immune responses, the hypervariable genes of the Major Histocompatibility Complex (MHC) have become a paradigm for investigating the evolution and maintenance of genetic (adaptive) diversity, contextually providing insight into the viability of wild populations, which is meaningful for conservation. Here, we provide the first preliminary characterization of MHC polymorphism and evolution in trouts from Albania, a known hotspot of Salmonid diversity harboring ecologically and phylogenetically distinct native (threatened) taxa. Overall, 36 trout—including Lake Ohrid-endemic Salmo ohridanus and S. letnica, and both riverine and lacustrine native brown trout (the S. trutta complex) from the Drin-Skadar drainage—were genotyped at the MHC-DAB locus through next-generation amplicon sequencing. We identified 34 alleles (including 30 novel alleles), unveiling remarkable population/taxon MHC-DAB distinctiveness. Despite apparent functional (supertype) similarity, S. letnica and the S. trutta complex showed MHC-typical high sequence/allele diversity and evidence of global/codon-specific positive selection, particularly at antigen-binding sites. Conversely, deep-water-adapted S. ohridanus revealed unexpectedly reduced allelic/supertype diversity and relaxed selection. Evolution by reticulation and signals of trans-species polymorphism emerged from sequence genealogies. Further investigations and increased sampling will provide a deeper understanding of the evolutionary mechanisms yielding the observed pattern of MHC diversity across Albanian trout taxa and populations.